On impulsive Sturm–Liouville operators with Coulomb potential and spectral parameter linearly contained in boundary conditions - Amirov, R. Kh.; Topsakal, N.; Guldu, Y. (Український математичний журнал, 2010)
The Sturm–Liouville problem with linear discontinuities is investigated in the case where an eigenparameter appears not only in a differential equation but also in boundary conditions. Properties and the asymptotic behavior of spectral characteristics are studied for the Sturm–Liouville operators with Coulomb potential that have discontinuity conditions inside a finite interval. Moreover, the Weyl function for this problem is defined and uniqueness theorems are proved for a solution of the inverse problem with respect to this function.